The Effect of Digitalization on Unemployment in Indonesia: Analysis of 33 Provinces for the Period 2013-2020 - Adryan, Naufal Fairuz; Al Muizzuddin Fazaalloh (Journal of Development Economic and Social Studies, 2025)
The high unemployment rate in Indonesia, averaging 5.79% during 2013-2020, remains a critical issue. This study examines the impact of digitalization on unemployment across 33 provinces, incorporating Regional Minimum Wage and Gross Regional Domestic Product (GRDP) as control variables. Using panel data analysis from the Central Bureau of Statistics, the findings reveal that digitalization and regional economic growth significantly reduce unemployment. A 1% increase in digitalization decreases unemployment by 0.55%, while a 1% rise in GRDP reduces it by 0.78%. However, minimum wage policies show no significant effect. The model explains 83.91% of the variation in unemployment rates. This research contributes to the literature by providing empirical evidence on the role of digitali zation in reducing unemployment at the regional level. The results highlight the importance of policies promoting digital transformation and strengthening regional economies to address unemployment effectively.